Zirconium-Catalyzed Alkyne Carbo- and Cycloalumination Reactions in Stereoselective Preparation of 1-Alkenyl Selenides - Kadikova, Rita N.; Ramazanov, Ilfir R.; Vyatkin, Alexey V.; Dzhemilev, Usein M. (Synthesis, 2017)
The Cp2ZrCl2-catalyzed methylalumination and сycloalumination of 1-alkynyl selenides followed by deuterolysis or hydrolysis affords corresponding (Z)-1-alkenyl selenides in high yields. Alternatively, (E)-1-alkenyl selenides were prepared by the reaction of 1-alkenylaluminums with organic diselenides in a one-pot procedure starting from the corresponding 1-alkynes, which provides a versatile tool for the preparation of stereo-defined unsaturated organic derivatives of selenium.
Keywords: alkynyl selenides; alkenyl selenides; vinyl selenides; alkenylaluminums; methylalumination; сycloalumination; zirconocene catalysis